The state of telepathology in Japan - Takashi Sawai; Miwa Uzuki; Akihisa Kamataki; Ikuo Tofukuji (Elsevier, 2010)
Telepathology began in Japan in the early 1990s in response to advances in computing and telecommunications equipment development and a dearth of pathologists. Telepathology in Japan is most often used for rapid intraoperative pathological diagnosis using frozen section, followed by second opinions and consultation. Intraoperatively, telepathology is used to determine malignancy, metastasis of malignant tumors, and the extent of excision. Infrastructure and equipment has evolved from analog lines to digital lines like integrated services digital network (ISDN) and asymmetric digital subscriber line (ADSL), and recently to fiber optics. The use of communications satellites is also being considered. Image quality is being improved to Hi-Vision (HDTV), and from still images to real-time video. Digital microscopy has been introduced, and is used in education and consultation.